Radio frequency interference on nearby radio astronomical lines: relationship between wind speed and radio signal strength measured at East Coast of Peninsular Malaysia - Sharifah Nurul Aisyah Syed Zafar,; Nor Hazmin Sabri,; Roslan Umar,; Zainol Abidin Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The East coast of Peninsular Malaysia receives a strong wind speed, heavy rain and high humidity during the Northeast monsoon. The Malaysian Meteorological Department claims that the wind speed during the Northeast season could reach 55.56 km/h or more. This strong wind speed and heavy rain could contribute to the attenuation of radio signals. This paper investigated the relationship between wind speed (km/h) and radio signal strength, RSS (dBm). The statistical correlation was employed to identify the correlation value and strength between them. The wind speed and RSS were collected during wet and dry seasons at Kusza Observatory, while the Spectrum analyser was used for measuring RSS (dBm) and the weather station for wind speed (km/h). The result showed that the wet season has strong and significant correlation compared to the dry season. Frequencies of 382.5 MHz, 945 MHz and 2160 MHz with correlation values of r = -0.583;-0.631 and -0:514, respectively, showed strong, negative and significant correlations with wind speed in the wet season. As for the dry season, only a frequency of 382.5 MHz showed a strong, positive and significant correlation with r = 0.555, while small and medium for others. This finding is useful to a radio astronomer to help determine the best period for radio astronomy observation with the lowest interference considering the weather in the East Coast of Peninsular Malaysia. Besides, this finding benefits a spectrum of users involved in mobile telecommunication, wireless internet, radio TV transmission and satellite broadcasting.